The first university e-learning study programme based on the adaption of the EUPC: Portuguese Implementation Study - Henriques, S.; Burkhart, G.; Miovsky, M. (Aditktologie, 2019)
BACKGROUND: The training curriculum has been developed by a European project (UPC-Adapt) cofunded by the European Commission. Eleven partners adapted the Universal Prevention Curriculum to suit the European context. AIMS: The aims of the implementation study were to adapt the EUPC into a standardised university course delivered by distance learning by Universidade Aberta (UAb) and develop a process evaluation study focused on this adaptation process. METHODS: The methodology was inspired by the WHO guidelines for the evaluation of prevention and treatment programmes and combined with qualitative research strategies and methods (observation and qualitative content analysis). PARTICIPANTS: It features distance learning, without geographical borders or physical barriers, which is particularly important for prevention professionals working in the far-flung Portuguese-speaking environment. RESULTS: Enrolment has been difficult, probably for three reasons: i) people tend to believe that they know everything about prevention, ii) the prevention of substance use might be too narrow a field, and iii) there is no perceived need for a specific qualification in order to do prevention work in Portugal. CONCLUSIONS: EMCDDA staff with proficiency in Portuguese had access to the training course and followed the development of the e-activities and the interaction within the virtual community as part of the evaluation protocol. The course represents the first real e-learning-based university adaptation running in a standard regime in Europe, and UAb (Portugal) has joined Charles University (Prague) in making effective use of programmes and materials based on the original UPC curricula in the university context.